1995
DOI: 10.1037/0022-3514.68.6.1152
|View full text |Cite
|
Sign up to set email alerts
|

Overly positive self-evaluations and personality: Negative implications for mental health.

Abstract: The relation between overly positive self-evaluations and psychological adjustment was examined. Three studies, two based on longitudinal data and another on laboratory data, contrasted self-descriptions of personality with observer ratings (trained examiners or friends) to index self-enhancement. In the longitudinal studies, self-enhancement was associated with poor social skills and psychological maladjustment 5 years before and 5 years after the assessment of self-enhancement. In the laboratory study, indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
605
6
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(644 citation statements)
references
References 48 publications
(68 reference statements)
25
605
6
6
Order By: Relevance
“…Earlier research has shown that narcissists are seen as less likable over longer periods of time (Colvin, Block, & Funder, 1995;Paulhus, 1998), yet we find that the highest-paid CEOs are those who are highest in narcissism and with the longest tenure. This suggests that while narcissists may be less likable, their sensitivity to criticism and low empathy may help them eliminate those who might challenge them or fail to acknowledge their brilliance.…”
Section: Discussionmentioning
confidence: 33%
“…Earlier research has shown that narcissists are seen as less likable over longer periods of time (Colvin, Block, & Funder, 1995;Paulhus, 1998), yet we find that the highest-paid CEOs are those who are highest in narcissism and with the longest tenure. This suggests that while narcissists may be less likable, their sensitivity to criticism and low empathy may help them eliminate those who might challenge them or fail to acknowledge their brilliance.…”
Section: Discussionmentioning
confidence: 33%
“…Although self-enhancers may be interpersonally offensive (Colvin et al, 1995;John & Robins, 1994;Paulhus, 1998), they are viewed by others as no better or worse adjusted than average. Other readers might argue that neither self-ratings nor informant ratings will suffice: Clinical expert judges are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that critics were correct (e.g., Colvin et al, 1995;John & Robins, 1994), over-claiming should show a negative association with adjustment.…”
Section: Study 4 Application To the Positive Illusions Debatementioning
confidence: 99%
“…Other research demonstrates that people whose views of themselves are overly favorable, relative to reports by independent observers or peer informants, show numerous psychological and social difficulties, both longitudinally and cross-sectionally ( Colvin, Block, & Funder, 1995 ). For example, men who were highly self-enhancing at age 18 were described by observer Q sorts at age 23 as having fluctuating moods, being deceitful and distrustful, and having brittle defenses.…”
Section: Other Studies Documenting Unconscious Emotional Processesmentioning
confidence: 99%